Nuclear magnetic resonance metabolomics approach in chemical and protective evaluations of Orthosiphon stamineus Benth. leaf extracts on cisplatin-induced nephrotoxicity - Pariyani, Raghunath (2016)
Orthosiphon stamineus (OS), locally known in Malaysia as ‘Misai Kucing’, is a herbaceous shrub belonging to the family Lamiaceae. Dried leaves of OS is gaining wide acceptance and marketed in the form of herbal tea, known as Java tea, owing to its traditional and scientific claims on various health benefits. OS has been a wellknown renoprotective agent primarily due to its diuretic potential. This research investigated the effects of commonly employed drying methods of OS leaves on their chemical constituent profile, and in vivo biological properties of the protective role in cisplatin induced nephrotoxicity using rats, through Nuclear Magnetic Resonance (NMR) metabolomics approach. The NMR spectra of rat urine and the OS leaf extracts were analysed and correlated using multivariate data analysis techniques employing metabolomics platform. The 1H NMR metabolite profiling of aqueous extract of OS leaves resulted in the identification of 31 metabolites. The presence of biologically active secondary metabolites including phenylpropanoids such as caffeic acid, protocatechuic acid, chlorogenic acid, flavonoids such as luteolin and apigenin, gallic acid and orthosiphol derivatives were confirmed by J resolved NMR technique. The HPLC - MS/MS analysis further confirmed the presence of these secondary metabolites. Metabolite fingerprinting in combination with multivariate analysis has successfully differentiated the three differently dried (Freeze, microwave and shade) OS leaves and established that the levels of 15 metabolites were varied significantly between the samples. The shade drying method retained maximum secondary metabolites followed by the microwave, while freeze drying retained the least. Assessment of the main beneficial properties, such as antioxidant, total phenolic and flavonoid contents of any tea preparation, confirmed that all the differently dried Java tea leaves gave good antioxidant activity, with the shade dried leaves recorded the highest level with an IC50 of 48.09 μg/mL. The chemical constituents correlated to the high antioxidant activity of the shade dried leaves were extracted from a Partial Least Square regression (PLS) model. In addition, the toxicity profile of the microwave dried OS leaves was investigated through acute oral toxicity test in Sprague Dawley (SD) rats of both sexes, whereby, the no-observed-adverse-effect level (NOAEL) of aqueous, 50% ethanolic and ethanolic extracts of the microwave dried OS was determined as 5000 mg/kg body weight/day. Thus, it is presumed that the microwave dried leaves are safe to be used as an oral health supplement. Cisplatin is an anticancer drug, which induces nephrotoxicity in a long term use. Metabolomic analysis of the rats’ urine revealed the involvement of a total of 17 biochemical markers from TCA cycle, carbohydrate, amino acid, and polyamine metabolic pathways in cisplatin nephrotoxicity. To the best of knowledge, 6 of the 17 involved metabolites are newly established in this study. In order to evaluate the protective efficacy of OS in cisplatin nephrotoxicity, shade and microwave dried OS extracts were administered at doses of 100, 200 and 400 mg/kg body weight to rats. The results suggested the dose independency of the extracts. Treatment with 50% aqueous ethanolic extract of shade dried OS leaves (OSFS) exhibited moderate ameliorative effect observed through a statistically significant reduction in the levels of 8 biomarkers. It was also revealed that the aqueous extract of the shade dried leaves (OSAS) exhibited slightly deteriorative activity via disturbance in the energy metabolism and gut microflora. The higher concentration of the secondary metabolites such as caffeic acid, chlorogenic acid, protocatechuic acid and orthosiphol in OSFS could be correlated to the ameliorative activity as revealed from a Principal Component Analysis (PCA) between OSAS and OSFS. A prediction model on nephroprotective effect of OS was constructed through PLS regression analysis. Thus, the impact of different drying techniques on chemical constituents of OS leaves was established. The metabolomics approach has proved to be successful in shedding light to the even minute variations in the biological profiles of the low intensity metabolites involved in the renal toxicity caused by cisplatin. A global comprehensive view of the OS effect in cisplatin toxicity was successfully profiled and correlated.